The Impact of Food Inflation On Urban Poverty And Its Monetary Cost : Some Back-Of-The-Envelope Calculations - Dessus, Sébastien (The World Bank, 2008)
This paper uses a sample of 73 developing countries to estimate the change in the cost of alleviating urban poverty brought about by the recent increase in food prices. This cost is approximated by the change in the poverty deficit, that is, the variation in financial resources required to eliminate poverty under perfect targeting. The results show that, for most countries, the cost represents less than 0.1 percent of gross domestic product. However, in the most severely affected, it may exceed 3 percent. In all countries, the change in the poverty deficit is mostly due to the negative real income effect of those households that were poor before the price shock, while the cost attributable to new households falling into poverty is negligible. Thus, in countries where transfer mechanisms with effective targeting already exist, the most cost-effective strategy would be to scale up such programs rather than designing tools to identify the new poor